STUDENTS’ EFL ANXIETY IN LEARNING READING IN ACEH, INDONESIA - Nina Afrida; Shafrida Wati (Lingua, 2022)
This research examines students’ foreign language anxiety of the English education of state institute of Islamic studies Langsa, Aceh, Indonesia which includes reading anxiety. Furthermore, this research also explores the factors that cause the emergence of anxiety experienced by students when learning a foreign language and explores their efforts to manage this anxiety. This research uses mix-methods with a sequential explanatory model. A total of 130 students for the 2019/2020 academic year at all semesters as the subject in this study. A questionnaire is given for them to obtain the quantitative data, besides, 30 sutudents get in-dept interview as the addition data to find the causes oh anxiety. Consequently, the results of questionnaire showed that Efl students experienced anxiety in learning reading is medium category(54.8%).While the result of in-depth interviews is among the factors that cause anxiety are cognitive factors, namely inadequate mastery of language supporting elements, such as vocabulary, grammar, and pronunciation, worry factors about getting negative assessments from the surrounding environment, low interest and motivation in foreign languages, assessment factors, and lecturer factors. Among the symptoms of anxiety experienced when learning a foreign language are shaking, heart palpitations, tension, confusion, cold sweats, panic, depression, and difficulty breathing. Not all Efl students make efforts to suppress anxiety, but some of them make preparations in the form of notes before showing the language, practice the language with friends and family, and follow several YouTube channels related to language learning.